Film dan politik di Indonesia 1957-64; Hambatan peredaran "Pagar kawat berduri" dan "Anak perawan di sarang penjamun" - Syahdu, Mahda Sofa (Wacana, Journal of the Humanities of Indonesia, 2002)
This study attempts to discuss the offensive policy taken by Partai Komunis Indonesia (Indonesian Communist Party) in cultural sphere, especially in film during the period of Demokrasi Terpimpin (1957-64). One of the implementation of the policy was the decision to stop the circulation of two films, Pagar Kawat Berduri and Anak Perawan di Sarang Penyamun, written by Asrul Sani and Usmar Ismail. By analyzing varios written and audio-visual sources, this study concludes that the reason were more political. Film was not seen as a form of art, but was suspected as a threat to the political power of the party.